When and how does sales team conflict affect sales team performance? - USLU, AYPAR (SPRINGER, 2014)
Drawing on information processing theory, this study integrates the conflict and learning literatures to examine an under-examined area in sales research: When do sales team task and relationship conflicts influence sales team performance, and what is the underlying process by which this occurs? Although there is burgeoning interest in sales research at the team level, very few empirical studies have shed light on sales team dynamics such as conflict and how they impact sales team performance. This study attempts to address this gap by developing a mediated moderation model and finds that (a) task and relationship conflicts have negative impacts on sales team performance, (b) team information exchange and information interpretation/implementation mediate the negative relationship between task and relationship conflicts and sales team performance, and (c) task and relationship conflicts stifle sales team performance when the team makes little use of a collaborative conflict handling style because this interactive combination (task/relationship conflict-low collaborative conflict handling style) hinders team information exchange and interpretation/implementation. Implications for conflict management in sales teams are discussed.
Keywords: Team task conflict; Team relationship conflict; Collaborative conflict handling style; Team information exchange; Team information interpretation and implementation; PRODUCT DEVELOPMENT; FIRM PERFORMANCE; INTRAGROUP CONFLICT; MARKET ORIENTATION; MANAGEMENT; KNOWLEDGE; WORK; CONSEQUENCES; ANTECEDENTS; PERCEPTIONS